Beyond reliable: challenging and deciding expert admissibility in U.S. civil courts. (10th October 2017) - O'Brien, Timothy L
Abstract: This article compares the effectiveness of several approaches to excluding expert testimony from court. Existing studies of judicial gatekeeping focus primarily on experts' reliability while often overlooking other substantive and procedural requirements for admissible expert evidence. However, an analysis of judicial decisions from civil rights cases in U.S. district courts ( n = 203) reveals that compared to reliability challenges, allegations that witnesses are not sufficiently qualified, that their opinions are irrelevant and that they have violated procedural rules are each more likely to result in the exclusion of experts' testimony. These findings suggest that exclusionary motions may be most fruitful when they target issues other than experts' reliability. This article also illustrates that a complete understanding of judicial gatekeeping must account for the full range of opportunities for contesting expert admissibility.